Routine use of denosumab for prevention of skeletal-related events in patients with bone metastases from prostate carcinoma in Bulgaria: a prospective observational study - Antoaneta Tomova; Valentina Ianakieva; Katja Bjorklof; Adrian Olszewski; Miglena Petrova (Biotechnology & Biotechnological Equipment, 2024)
Bulgarian real-world data on denosumab use for the prevention of skeletal-related events (SREs) associated with bone metastases (BM) from prostate cancer (PC) are lacking. This observational study enrolled 100 adult PC patients with ≥1 BM receiving denosumab (EUPAS26983). Patients’ routine treatment was observed retrospectively for ≤6 months and prospectively for 12 months. Denosumab use and safety, SRE incidence, denosumab persistence (allowing ≤2 missed doses), and pain severity were evaluated using descriptive statistics. Denosumab was initiated at a median (Q1, Q3) of 1.8 (0.6, 9.6) months following BM diagnosis with earlier initiation in hormone-sensitive (HSPC; 1.5 [0.6; 4.2]; n = 74) than castration-resistant PC (CRPC; 7.9 [0.8; 16.4]; p = .082; n = 26) and in younger (<65 years; 1.2 [0.3; 2.8]; n = 19) than older patients (≥65 years; 2.0 [0.7; 9.6]; p = .161; n = 81). Ten SREs were recorded during the retrospective and 10 during the prospective period; none were symptomatic. Denosumab was used for a median of 472 (387, 599) days overall and for 443–464 days without missing more than two doses (persistence). The proportion of patients reporting acceptable pain (score ≤4 of 10) increased from 6% at baseline to 22% at month 12. Twenty-four denosumab-related adverse events were reported, 2 were serious (osteomyelitis, osteitis) and 5 were related to osteonecrosis of the jaw. In Bulgarian clinical practice, denosumab use was associated with the prevention of symptomatic SREs and pain improvement. Denosumab was mostly used persistently. No symptomatic SREs were reported. Safety findings were consistent with previous reports of denosumab use in PC.